Alfalfa crop coefficients developed using a weighing lysimeter in southeast Colorado - AlWahaibi, Hamdan, author; Andales, Allan, author; Straw, Dale, author; Simmons, Lane, author; Bartolo, Michael, author; Ley, Thomas, author; Trout, Thomas, author; Chávez, José, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Weighing lysimeters are precise devices used to measure crop evapotranspiration (ET) and to develop crop coefficients. A weighing lysimeter was installed in the Arkansas River Valley of Colorado in 2006 to measure ET and develop crop coefficients of locally-grown crops. The lysimeter was filled with a 3 m × 3 m undisturbed soil monolith. Alfalfa (Medicago sativa L.) was planted in the lysimeter and in 4 ha of surrounding field in August 2007. Climatic data and soil conditions were measured using microclimate and soil sensors installed above and on the lysimeter. Furrow irrigation was applied to the monolith and surrounding field. Reference ET was calculated using the hourly ASCE standardized reference ET equation. Crop coefficients of alfalfa were calculated by dividing daily measured ET from the lysimeter by the corresponding daily total ASCE standardized reference ET. Four alfalfa cuttings occurred in both the 2008 and 2009 growing seasons. The results showed that the alfalfa growth, climate and precipitation were shaping crop coefficients. The first cutting cycle, which had slower growth due to climate, had lower crop coefficients, whereas later cutting cycles with rapid growth had higher crop coefficients. The maximum crop coefficients were below 1.2 in 2008 and at or above 1.2 in 2009. Precipitation interception by the alfalfa canopy increased evaporation and caused outliers in the crop coefficient values.
Meeting irrigation demands in a water-challenged environment
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.